DETERMINAN MINAT MAHASISWA DALAM MELAKUKAN INVESTASI SYARIAH - Rinwantin, Rinwantin; Pujiastuti, Yanti (Sekolah Tinggi Ilmu Ekonomi Bank BPD Jawa Tengah, 2020)
Increasing student interest in investing in sharia is needed. This study aims to determine the effect of investment training, risk perception, and knowledge on student interest in investing in sharia. The research was conducted on students who were members of the Islamic Economics Study Group in Semarang. A total of 70 students were taken as samples with accidental sampling. The analysis technique used in this research is multiple linear regression analysis. The results showed that investment training and perceptions of risk had a positive and significant effect on students interest in sharia investing. Meanwhile, the investment knowledge variable has no effect on student interest to invest in Sharia. The most dominant variable in influencing interest students to investing in Sharia in Semarang is investment training. The coefficient of determination of 0.718 indicates that interest in investing in sharia is influenced by training, perceptions of risk and knowledge of 71.8%, while 28.2% is influenced by other factors outside the model. Therefore, efforts to increase students interest to investing in sharia can be done by providing training and understanding to students regarding perceptions of risks in investing in Sharia.